The Effectiveness of Application of Marriage Law in Polewali Mandar District: Polewali Religious Court Case Study - Riswan, Riswan (Al-Iftah: Journal of Islamic studies and society, 2020)
This paper discusses the effectiveness of the implementation of Law of the Republic of Indonesia Number 16 of 2019 concerning Amendments to Law No. 1 of 1974 concerning Marriage in Polewali Mandar. There are at least three problems that are studied in this paper, namely, first, the problem of dispensation for marriage in the Polewali Religious Court after the enactment of Law Number 16 of 2019. Second, Judges' Considerations in Deciding on Marriage dispensation cases in the Religious Courts. Third, the Effectiveness of the Implementation of Law Number 16 of 2019 Against Marriage Dipensation Cases at the Polewali Religious Court. By using a qualitative descriptive method sourced from primary and secondary data through observation, interviews, and documentation techniques, it was found thatthere was a significant increase in cases of filing for dispensation for marriage after The enactment of Law Number 16 of 2019. Second, the judge's considerations in granting the marriage dispensation request judges are more dominant because they protect the benefit and avoid harm. In addition, Islam also recommends not to make it difficult for someone to get married. Third, the application of Law Number 16 of 2019 to the marriage dispensation is still less effective in the Polewali Mandar Regency community.